2020
DOI: 10.1177/0961203320937472
|View full text |Cite
|
Sign up to set email alerts
|

Rubrics for mortality: a real-world observational long-term lupus nephritis cohort

Abstract: In this study, we aimed to evaluate long-term patient survival according to demographic data, clinical manifestations of systemic lupus erythematosus (SLE) and previous and current treatments, collected retrospectively. Patient selection required a minimum of four American College of Rheumatology revised criteria for SLE, biopsy-proven lupus nephritis (LN) available for reclassification according to the modified National Institutes of Health proposal for activity and chronicity indices and a minimum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…As shown in Figure 2(a), the mortality depended on the final renal function, which was the independent predictor for mortality identified in multivariate Cox proportional hazards analysis, and differed significantly between the groups. However, contrary to previous studies, 12,39 the mortalities depended on the histologic type, CYC usage, and HCQ usage were not differed significantly between the groups. This result was consistent with the conclusion of our study that if each patient received appropriate treatment according to the guidelines, response to treatment and prevention of renal function decline are more important than specific histological findings and treatment methods.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure 2(a), the mortality depended on the final renal function, which was the independent predictor for mortality identified in multivariate Cox proportional hazards analysis, and differed significantly between the groups. However, contrary to previous studies, 12,39 the mortalities depended on the histologic type, CYC usage, and HCQ usage were not differed significantly between the groups. This result was consistent with the conclusion of our study that if each patient received appropriate treatment according to the guidelines, response to treatment and prevention of renal function decline are more important than specific histological findings and treatment methods.…”
Section: Discussioncontrasting
confidence: 99%
“…9 Other studies reported that baseline C3 and C4 levels were significantly lower in patients who died. 23 Pathology parameters such as proliferative type pathology 12 and a higher index of activity 10,12 were known to predict mortality. Failure to reach CR is a known risk factor for mortality in 12 months 9,10,12 or 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations